The consequences of thyroid gland dysfunction and its impact on the lifestyle os those affected (Research, Society and Development, 2024)
Objective: The article aims to describe the pathophysiology of syndromes that result from hypo- and hyperfunction of thyroid hormones and their respective consequences. Methods: This article is a bibliographic review, whose research was carried out in bibliographic material, in the books: Principles of Internal Medicine and Clinical Endocrinology, and in articles available in electronic databases: Scielo, PubMed, and Lilacs. Articles published in the last 23 years, available in full text for free and in Portuguese, English, and Spanish were selected. Those experimental studies, articles not available in full text, and produced outside the specified period were excluded. Results and Discussions: The thyroid gland produces the hormones T3, T4, and calcitonin, which are essential in maintaining the body's homeostasis. Gland function is regulated by the hypothalamic-pituitary-thyroid axis, where the TSH stimulates the synthesis and release of T3 and T4, and these inhibit TSH, via negative feedback. Modifications that affect the production and secretion of these hormones present a characteristic clinical picture of hyper or hypofunction. This is characterized by a reduction in the serum concentration of thyroid hormones, it´s main cause is Hashimoto's Thyroiditis. On the other hand, hyperfunction of the gland, called hyperthyroidism, involves increased release of T3 and T4 and is mainly caused by Graves' Disease. Conclusion: In this scenario, it becomes clear that the consequences of initiating thyroid dysfunction for the body are serious and can culminate in compromising the individual's quality of life and progressing to organic dysfunctions.